Is drug substitution always a solution? Phenytoin induced gingival enlargement - A case report - Chandni Gupta; Ritika Arora; Himani Sharma (Wolters Kluwer Medknow Publications, 2019)
Gingival enlargement is the most common side effect which is reported with the administration of the anti-epilepsy drug phenytoin (PHT). It is of vital importance as it greatly affects the esthetics and also interferes with the mastication and oral hygiene practices. It is now well known that the presence of gingival inflammation resulting from poor oral hygiene acts as a major risk factor and leads to worsening the condition. Therefore, the patients taking PHT should be made aware of the possible outcomes and the importance of maintaining oral hygiene and periodontal maintenance therapy. This case report describes a case of PHT-induced gingival enlargement in which surgical intervention was done to correct the gingival enlargement, and in spite of patient not discontinuing the drug (PHT), no recurrence of enlargement was seen even after 1 year.